1995
DOI: 10.12693/aphyspola.88.549
|View full text |Cite
|
Sign up to set email alerts
|

EPR and MMMA Study of C60upon K-Doping

Abstract: EPR and ΜΜMΑ studies of C60 upon K-doping have been performed. Two different and welł separated EPR narrow lines were detected for C1-60 and C at temperatures below 100 K. Time dependent changes in the intensities of both CL and C3-60 lines were observed when the system undergoes an eutectoid transformation. The evolution of superconductivity with two T' related to dicherent valences (v) of C6Ó ion radicals have been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This procedure (for x ≤ 3) leads to a decomposition of K 1 C 60 to α-C 60 and K 3 C 60 . The process is reversible in accordance with the eutectoidal phase diagram of K x C 60 [22][23][24][25].…”
Section: K X C 60supporting
confidence: 58%
“…This procedure (for x ≤ 3) leads to a decomposition of K 1 C 60 to α-C 60 and K 3 C 60 . The process is reversible in accordance with the eutectoidal phase diagram of K x C 60 [22][23][24][25].…”
Section: K X C 60supporting
confidence: 58%
“…The ε calculated for N 2 using Eqs. (2,4) for various temperatures, is shown as the dashed curve in Fig. 2.…”
Section: T (K)mentioning
confidence: 99%
“…Dielectric constant/loss measurements in these systems are particularly important because they directly probe the orientational ordering. However, only measurements at microwave frequencies have been performed in the case of solid N 2 [4]. The molecular rotations in these solids are strongly hindered, and as a consequence the relevant time scales for collective molecular reorientation are expected to be much larger than those for an ideal free rotor (∼10 −12 sec).…”
mentioning
confidence: 99%
“…Kempiflski et al [4] observed that during the first stage of intercalating the fullerene C60 by potassium, a new unstable phase with T c = 21 K occurs. Beside the stable-phase K3C60 with T c = 19 K, at the front of diffusion, when the lattice constant is higher, a* > a (K3C60), the less dense phase has higher T i > T c (K3C60).…”
Section: New Sc Phase In K~c60 At the First Stage Of Intercalationmentioning
confidence: 99%